Division of Competences and Responsibilities Between EU Institutions/ Agencies and Member States for Border Management - Maučec, Gregor (Migration and Central Europe: Challenges and Legal Responses, 2024)
In the European Union (EU), border control and surveillance have emerged as significant policies for managing migration. The EU’s action at the external borders is based on a combination of migration securitisation and externalisation of border management policies. The EU follows a ‘shared competence’ and ‘shared responsibility’ for developing an integrated European border management system in the context of migration control. This chapter examines the division of internal and external competences and responsibilities between EU institutions/agencies and national authorities of member states concerning border management and migration. Further, it analyses the intensity and scope of the EU’s intervention in this area along with its limitations. The European integrated border management is crucial for improving migration management and is conducted within a multi-level governance system with binding rules and various actors. This raises concerns regarding the exact allocation of competences and corresponding obligations and responsibilities conferred on each of them. The Schengen Borders Code (Regulation (EU) 2016/399) and the European Border and Coast Guard Regulation (Regulation (EU) 2019/1896) are the primary legally binding instruments, which specify common (supranational) rules governing the movement of persons across EU borders and highlight how member states manage their borders serving a common interest within an increasingly harmonised substantive and institutional framework. Although, the rules relating to the management of EU external borders continue to evolve in the context of the Schengen acquis, member states retain their own competences and responsibilities regarding border control and entry to their territories concerning the maintenance of legal and public order and national security. However, the member states are required to exercise their competence in this field in compliance with the objectives and acts of the EU’s border management and migration acquis and policies, ensuring full respect for fundamental rights.Keywords: European Integrated Border Management, European Border and Coast Guard (Frontex) Agency, member states’ border authorities, border management – migration regime nexus, fundamental rights, Court of Justice of the EU